Influence of the patient-practitioner interaction context on acupuncture outcomes in functional dyspepsia: study protocol for a multicenter randomized controlled trial - Seok-Jae Ko; Jae-Woo Park; Jungtae Leem; Ted J. Kaptchuk; Vitaly Napadow; Braden Kuo; Jessica Gerber; Laurie Dimisko; Inkwon Yeo; Junhee Lee; Jinsung Kim (BMC, 2017)
Abstract Background In the treatment of functional dyspepsia, the placebo effect has been reported to be high, and the influence of the patient-practitioner relationship may be a major component of this effect. The specific and non-specific effects of acupuncture cannot be easily distinguished, and the patient-practitioner relationship may influence the total therapeutic effect in clinical practice. There have been no studies that investigate the influence of patient-practitioner relationship on acupuncture treatment for patients with functional dyspepsia. Methods Patients with postprandial distress syndrome, a functional dyspepsia subtype, will be recruited at three hospitals (two in Korea and one in USA) for an international, multi-center, randomized, patient/assessor-blinded, clinical trial. The total anticipated sample size is 88. The participants will be randomly allocated into two groups: an augmented interaction group and a limited interaction group. Acupuncture, with total 12 acupoints, will be performed twice weekly for 4 weeks in both groups. Trained practitioners will provide an "augmented" or "limited" interaction context, as determined by random allocation. The primary outcome measure is the proportion of responders, the proportion of participants who answer "yes" to more than half of the adequate relief questions during the study. Secondary outcome measures include questionnaires for quality of life and symptoms of dyspepsia, and maximum tolerable volume of nutrient drink test. Data will be collected at baseline and following 4 weeks of acupuncture. Discussion This study will evaluate the influence of the patient-practitioner interaction on clinical effects of acupuncture in patients with functional dyspepsia. Trial registration CRIS Identifier: ( KCT0002229 ).